MACEINA’S POINT OF VIEW ON NEW PEDAGOGICAL TRENDS - Valatkienė, Stasė (Acta Paedagogica Vilnensia, 2008)
The article represents A. Maceina’s point of view on modern pedagogical trends. The method of comparative analysis was employed to find Maceina’s conception of classification of new pedagogical trends and his point of view on overall pedagogy’s history. The author underlines that the scientist was well familiar with the experience of foreign school, studied deeply the modern pedagogy of the beginning of the twentieth century (G. Kerðenðteinerio, H. Gaudigo, G. Vynekeno and others). Maceina accentuated three pedagogical trends: transcendental, psychological and vital. He not only analyzed the new trends critically, by but also marked out their strong (research of child psychic qualities, teaching activization, respect for child) and week (child’s action overrating, unsatisfactory attention to children spiritual upbringing and to education purposes) sides. The article emphasizes that Maceina criticized pedagogical vitality and disapproved of the blind copying of foreign experience for Lithuanian education reform.